Effect of auricular acupoint sticking and pressing therapy on preventing postoperative nausea and vomiting in patients undergoing thoracolumbar surgery under general anesthesia (耳穴贴压预防全身麻醉下胸腰椎手术患者术后恶心呕吐的效果研究) - CHEN Ying (陈英); XIE Wei (谢薇); YANG Mei (杨梅); REN Liwen (任丽雯); ZHANG Yating (张雅婷); YANG Ji (杨吉); REN Xiuya (任秀亚) (Association of Integrative Nursing, 2022)
Objective To observe the effect of auricular acupoint sticking and pressing therapy on preventing postoperative nausea and vomiting in patients undergoing thoracolumbar surgery under general anesthesia. Methods To retrospectively analysis the clinical data of 126 patients who underwent posterior thoracolumbar surgery under general anesthesia, including 37 patients who underwent auricular point sticking and pressing 24 hours before surgery (group A), 48 patients who underwent auricular point sticking and pressing after surgery(group B) and 41 patients without auricular acupoint sticking and pressing therapy after operation (group C). Incidence of postoperative nausea and vomiting and PONV scores were recorded at 8 h, 24 h and 48 h after operation. Results Among the three groups of patients, group A had the lowest incidence of postoperative nausea and vomiting, and the lowest PONV score. The incidence of PONV at 48h after operation was 35. 13%, which was significantly lower than that in the group C(P<0. 05). Compared with group C, PONV condition were improved to some extent in group B, and the incidence of PONV at 8h, 24h, and 48h after operation were 41. 67%, 47. 92%, and 35. 42%, respectively, lower than those in the group C(P<0. 05). There was no significant difference in the incidence and PONV score between group A and group B (P＞0. 05). Conclusion Auricular acupoint sticking and pressing therapy in perioperative period can reduce the incidence of postoperative nausea and vomiting in patients with thoracolumbar surgery, and reduce the incidence of related complications. However, the incidence of postoperative nausea and vomiting was still high after implementation of auricular acupoint sticking and pressing therapy alone. (目的 观察耳穴压贴压预防全身麻醉下胸腰椎手术患者术后恶心呕吐的效果。方法 回顾性分析2020年2月-12月医院收治的全身麻醉下行胸腰椎后路手术的患者126例, 其中术前24 h行耳穴贴压患者37例(A组)、术后行耳穴贴压48例(Ｂ组)和未行耳穴贴压41例(C组); 记录术后8 h、24 h、48 h恶心呕吐情况及术后恶心呕吐(PONV)评分。结果 A组术后恶心呕吐发生例数、发生率及PONV评分最低, 术后48 h PONV的发生率为35. 13%(13/37), 与C组相比, 差异有统计学意义(P＜0. 05)。B组较C组患者术后恶心呕吐情况有一定改善, 术后8 h、24 h、48 h的PONV的发生率分别为41. 67%(20/48)、47. 92%(23/48)、35. 42%(17/48), 差异有统计学意义(P＜0. 05); A组与B组患者PONV发生例数、发生率及PONV评分结果比较, 差异无统计学意义(P＞0. 05)。结论 胸腰椎手术患者围手术期给予实施耳穴贴压, 可降低术后恶心呕吐的发生风险, 减少其相关并发症的发生, 但实施单纯耳穴贴压后其PONV的发生率仍较高。)